Research on the composition development of suppositories with echinacea and study of their stability - I. V. Herasymova; H. B. Yurieva; T. H. Yarnykh; D. V. Voronenko (Український журнал військової медицини, 2022)
The purpose of the work was to experimentally substantiate the composition and study the stability of extemporal suppositories with Echinacea, intended for use in complex therapy and prevention of genitourinary diseases.